〖Sb〗_2 O_3-〖Na〗_2 O-〖WO〗_3دراسة تأثير التنغستن على الخصائص البنيوية و الضوئية للزجاج ذو التركيبة - سنوقة, مسعودة (جامعة الوادي University of Eloued, 2019)
إن استعمالات الزجاج في حياتنا اليومية, وفي مجال الصناعات التكنولوجية العالية أصبح من الأساسيات التي لا يمكننا الاستغناء عنها، حيث صنفت هذه المادة مؤخرا ضمن المواد ذات التطبيقات الدقيقة، عالية التخصص، في التقنيات الالكترونية أو البصرية (ليزر)، وعليه وددنا في مذكرتنا هذه اجراء بحث بسيط حول هذه المادة من خلال عرضنا في بداية عموميات حول الزجاج من خلال اعطاء تعريف بنيوي واستخلصنا عندها بأن الزجاج هو مادة صلبة لا بلورية تتميز بظاهرة الانتقال الزجاجي. كما قمنا أيضا بذكر وعرض بعض أنواع الزجاج من حيث تركيبته وإعطاء مميزات لكل نوع. بعدها تطرقنا إلى عرض بعض الطرق التجريبية الأكثر استخداما لإجراء الخصائص الفيزيائية و الضوئية لزجاج كفحص بالأشعة السينية، مطيافية تحت الحمراء، الكثافة، قرينة الانكسار و طيف الامتصاص.وفي الأخير قمنا بتحضير عينة زجاجية بتركيبة (80-x)Sb2O3-20Na2O-(x)WO3 و اجرينا عليها دراسة خصائص الفيزيائية منها البنيوية والضوئية .ومن هنا نستخلص أن الزجاج هي مادة صلبة سهلة التحضير وسهلة التعامل مع تركيبتها حيث تمكننا من تحسين وتعديل خصائصها من خلال تغير في مكوناتها.The use of glass in our daily lives, and in the field of high-tech industries has become a indispensable principle. This article has recently been classified into the materials with highly specialized applications in electronic or optical technologies. A simple research on this material through our presentation at the beginning of the generalities about the glass by giving a structural definition and then concluded that the glass is a solid non-crystalline characterized by the phenomenon of glass transition.We also mentioned and presented some types of glass in terms of composition and give advantages to each type. Then we discussed some of the most experimental methods used to conduct physical and optical properties of glass such as x-ray, infrared spectroscopy, density, refractive index and absorption spectra.In the end, we prepared a glass sample with the composition of (80-x)Sb2O3-20Na2O-(x)WO3 and examined the physical properties of the structural and optical.From this we conclude that glass is a solid material easy to prepare and easy to deal with the composition, which enables us to improve and modify their properties through a change in the components.
مذكرة ماستر تخصص فيزياء
Keywords: الكلمات المفتاحية: البلور،الزجاج، الانتقال الزجاجي، درجة الانصهار، التبريد، طيف الامتصاص; crystal, glass, glass tr crystal, glass, glass transition, melting point, cooling, absorption spectrumansition, melting point, cooling, absorption spectrum